Table of Contents (Law, State and Telecommunications Review, 2021)
We are delighted to include articles on the data controllers’ role in Artificial Intelligence training under the European Union General Data Protection Regulation, the data protection issues raised by the Covid-19 Pandemic, the level of protection offered by cyberspace laws in Pakistan, the use of algorithmic intervention in public interest decision-making in Colombia, the use of electronic media in the production of investigative actions in Russia, the role of media coverage in armed conflicts, the use of information and communication technologies in Kazakh Civil Law, the correlation between internet access and education access in Colombia, the differences between the evaluation of electronic and documentary evidence, and the different types and applications of the Internet of Things.